User's guide to rapid prototyping - Grimm, Todd (Society of Manufacturing Engineeers, 2004)
"User's Guide to Rapid Prototyping will help designers, engineers, executive management, and others in the company understand how to apply rapid prototyping technologies such as 3D printing, stereo-lithography, selective laser sintering, and fused deposition modeling to the product development process. Intertwined with rapid prototyping, the processes of rapid tooling and rapid manufacturing are also discussed." "An aid to making informed business decisions, the book provides information about when it may be right to implement rapid prototyping in-house versus going to a service provider. The path through justification, evaluation, and implementation is outlined. Readers will gain insights into the benefits, risks, and limitations of each technology."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved